Women and the reformations a global history - Wiesner, Merry E. 1952- (New Haven London Yale University Press, 2024)
"A compelling, authoritative history of how women shaped the Reformations and transformed religious life across the globe. The Reformations, both Protestant and Catholic, have long been told as stories of men. But women were central to the transformations that took place in Europe and beyond. What was life like for them in this turbulent period? How did their actions and ideas shape Christianity and influence societies around the world? In this rich and definitive study, renowned scholar Merry E. Wiesner-Hanks explores the history of women and the Reformations in full for the first time. Wiesner-Hanks travels the globe, examining well-known figures like Teresa of Avila, Elizabeth I, and Anne Hutchinson, as well as women whose stories are only now emerging. Along the way, we meet converts in Japan, Spanish nuns in the Philippines, and saints in Ethiopia and America. Wiesner-Hanks explores women's experiences as monarchs, mothers, migrants, martyrs, mystics, and missionaries, revealing that the story of the Reformations is no longer simply European;and that women played a vital role." --
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Women in Christianity -- 16th century; Women in Christianity -- 17th century; Reformation -- Biography; Counter-Reformation -- Biography; Christian women -- Religious life; Women -- Religious life; Christentum; Christianity; Early modern history: c 1450/1500 to c 1700; European history; Europäische Geschichte: Reformation; Gender Studies: Frauen und Mädchen; Gender studies: women; Geschichte der Religion; HIS058000; HISTORY / Europe / General; HISTORY / Social History; History of religion; Religion / Christianity / History; RELIGION / Sexuality & Gender Studies; SOCIAL SCIENCE / Women's Studies; Social & Cultural History; Sozial- und Kulturgeschichte; Contre-Réforme - Biographies; Femmes - Vie religieuse; Femmes dans le christianisme - 16e siècle; Femmes dans le christianisme - 17e siècle; RELIGION / Christianity / General; Biographies; Biographies